Malaysian dolomite modification for hydrogen production enhancement and carbon dioxide emission reduction via oil palm frond gasification - Abdul Rahim, Nur Faizal (2014)
As the world production of crude oil is expected to be depleted in the near future, many researchers embarked on tremendous kinds of research to find the most propitious replacement for the world current energy and hydrogen is prescribed as renewable energy with zero net greenhouse gases emission and found abundantly as a feedstock. In addition, the feedstock obtained from various source of agricultural wastes provide huge advantage for this kind of energy due to sustainable and renewable aspects. This research aimed to enhance the production of hydrogen by using gasification method by utilizing oil palm fronds as a feedstock in the presence of catalysts. Firstly, calcined dolomite was undergone mechanochemical treatment under different media (air, ethanol and water) to deform its physical properties like surface area and grain size. The physical and chemical properties of treated dolomites were characterized by using X-ray diffraction (XRD), BET surface area (SBET), thermal gravimetric analysis (TGA), field emission scanning electron microscope attached with energy dispersive X-ray (EDX-FESEM) and the catalytic test is been carried out using temperature programmed gasification (TPG). Results, the treatment improves catalytic activity significantly which can be seen from TPG spectra and H2 cumulative bar chart. Moreover, the cumulative CO2 substantially decreased at the end of the reaction. This is mostly due to the treatment effect especially using water as a media in milling process which increased the dolomite catalyst surface area from 13 m2/g to 22 m2/g made it became superior for H2 production as well as reducing CO2 emission from the gasification reaction. Secondly, the modification of the dolomite was extended to the introduction of promoters on the calcined dolomite phase. Potassium (K), cerium (Ce), nickel (Ni), iron (Fe) and cobalt (Co) were all been selected for the purpose of this study. All these metals in the form of metal nitrate undergone wet impregnation method with calcined dolomite. The catalysts were denoted as K/CD, Ce/CD, Ni/CD, Fe/CD, Co/CD according to their chemical formula and CD is represented as calcined dolomite. All the catalysts been characterized by aforementioned method with additional gas product ratio (H2/CH4) parameter because to find out the most efficient catalyst able to give quality of the product-end. The promoters have been detected on the phase of calcined dolomite and been confirmed with XRD pattern. Meanwhile, from BET surface area result showed the pore size diameter increased which leads to increase in surface area and this confirmed by referring to the transmission electron microscopy. All dopants improved H2 production significantly which can be seen from TPG profile where potassium dopant showed a promising result including gas product ratio study which it differs five times from the unpromoted ones. Overall, the results confirmed that the order of most active catalysts in the ascending order was CD < Ce/CD < Co/CD < Fe/CD < Ni/CD < K/CD.